Sexual abuse in minors, public health problem - Girón Sánchez, Rosario (2015)
This study systematized information on the size of sexual abuse, reviews the history, symptoms in the short and long term impact on mental health, as well as risk behaviors in this population, prevalence, detection consequences. While there is no limit to being a victim of sexual abuse, the age of greatest risk is at the stage of puberty, probably because at this age express the changes in physical and sexual development as well as the expansion of space socialization. The high number of dysfunctional families, points out the importance in our environment have these events in the genesis of this problem. In particular when the maternal model is a non-assertive woman, oppressed victim of domestic assault, unable to transmit behavioral skills to help their daughters to protect themselves.Sexual assault can occur in unpopulated areas and remote, but also in public places, crowded and close. It is common that the perpetrators are acquaintances and enjoyed the confidence of victims.